Funcionalidade dos extratos fenólicos obtidos pelo cultivo semi-sólido de resíduos de abacaxi (Ananas comusus L.) e goiaba (Psidium guajava L.) - Sousa, Bruno Alexandre de Araujo (2009)
Solid substrate cultivation (SSC) has become an efficient alternative towards rational use of agro industrial wastes and production of value-added products, mainly in developing countries. This work presents the production and functional application results of phenolic extracts obtained by solid substrate cultivation of pineapple (Ananas comosus L.) and guava (Psidium guajava L.) residues associated to soy flour and bioprocessed by Rhizopus oligosporus fungus. Two experimental groups were tested: (1) 9g of fruit residue and 1g of soy flour (A9 or G9); (2) 5g of fruit residue and 5g of soy flour (A5 or G5). After SSC, 100ml of distilled water was added to each Erlenmeyer flask containing 10g of bioprocessed material in order to obtain the phenolic extracts. Samples were taken every two days for total phenolic concentration (TPC) and antioxidant capacity evaluation by DPPH test during 12-day cultivation. The 2-day and 10-d ay extracts were selected and concentrated by ebullition until 1/10 of original volume was reached. After that, both non-concentrated and concentrated extracts were evaluated for their antimicrobial activity against Staphylococcus aureus and Salmonella enterica and a-amylase inhibitory capacity. It was observed an inverse relationship between total phenolic concentration (TPC) and antioxidant capacity during the cultivation. Besides that, the concentrated pineapple samples after two days were able to inhibit both pathogens tested, especially S. aureus. Guava concentrated extracts after 2 days showed expressive inhibition against S. enterica, but negative results against S. aureus growth. When it comes to a-amylase inhibition, A9 extracts after 2 days, both concentrated or not, completely inhibited enzyme activity. Similar behavior was observed for G9 samples, but only for concentrated samples. It was shown that concentration by ebullition positively affected the enzymatic inhibition of G9 and A9 samples, but on the other side, decreased antiamylase activity of A5 and G5 samples